Multivalent scaffolds induce galectin-3 aggregation into nanoparticles - Goodman, Candace K.; Wolfenden, Mark L.; Nangia-Makker, Pratima; Michel, Anna K.; Raz, Avraham; Cloninger, Mary J. (Beilstein Journal of Organic Chemistry, 2014)
Galectin-3 meditates cell surface glycoprotein clustering, cross linking, and lattice formation. In cancer biology, galectin-3 has been reported to play a role in aggregation processes that lead to tumor embolization and survival. Here, we show that lactose-functionalized dendrimers interact with galectin-3 in a multivalent fashion to form aggregates. The glycodendrimer–galectin aggregates were characterized by dynamic light scattering and fluorescence microscopy methodologies and were found to be discrete particles that increased in size as the dendrimer generation was increased. These results show that nucleated aggregation of galectin-3 can be regulated by the nucleating polymer and provide insights that improve the general understanding of the binding and function of sugar-binding proteins.
Keywords: dendrimers; galectin-3; glycodendrimers; multivalency; multivalent glycosylation; protein aggregation